A retrospective analysis of the national youth teams in volleyball: were they always faster, taller, and stronger? - Mostaert, M.; Pion, J.; Lenoir, M.; Vansteenkiste, P. (The Journal of Strength and Conditioning Research, 2022)
Although there are numerous studies comparing the characteristics of young and adult volleyball players of different levels, it remains unclear to what extent these findings can be used for performance prediction because very few are based on longitudinal or retrospective analyses. The aim of the current retrospective study was to test to what extent anthropometry, physical performance, and motor coordination can predict future selection in national youth teams. From 2012 to 2015, 1738 10- to 13-year-old boys and girls who played volleyball completed 3 anthropometric, 4 physical performance, and 3 motor coordination tests. In January 2020, 52 athletes of this sample were found to be part of one of the national youth teams of Belgium. A multivariate analysis of covariance, discriminant analyses, and logistic regression analyses were conducted to compare the test results of the selected vs. the nonselected players. Significance level was set at p = 0.05. Results showed that the selected players were already taller and showed better jumping performance, and for females, they tended to have better motor coordination at the time of baseline measurement. Therefore, it seems important to focus on the development of motor coordination and jumping performance at young ages because superiority in these characteristics increases the chances to be selected for the national team 4-8 years later. Nevertheless, considering the large variation in results, selection cannot be made based on these characteristics alone. The practical implications for coaches and federations with respect to training and talent detection are discussed.